Pré-hidratação de sementes de ervilha e sua interferência na avaliação do potencial fisiológico - Costa, Caroline Jácome (2007)
The present work had the objective of to study biochemical and physiological alterations in function of pea seed pre hydration with e phasis in the electrolyte leakage and in the expression of different isoenzymatic systems,trying to contribute for the i provement of the pre hydration methods of seeds to be submitted to tests for evaluation of its physiological potential.Seeds lots of cvs.Axé and Maria, characterized for the water content,germination,first ger mination counting,accelerated aging,electrical conductivity and seedling emergence in the field,were used.The seeds of each lot were pre hydrated in saturated atmosphere and hum idified substratu until they reach 10,12 and 14%of water content.After the pre hydration,the seeds were submitted to the tests of electrical conductivity,accelerated aging and leakage of calcium ,potassium and magnesium and characterized for the expression pattern of the isoenzymatic systems Malate Dehydrogenase,Acid Phosphatase,Glutamate Dehydrogenase and Glutamate Oxalacetate Transaminase.The pre hydration of the seeds using saturated atmosphere or humidified substratum see s to affect the process of restructuring the seed cellular e branes system differently,being reflected in alterations in the pattern of electrolyte leakage and Acid Phosphatase isoenzymatic expression.Discrepancies take place a ong results obtained by the test of electrical conductivity for evaluation of the physiological potential of pea seeds,depending on the proceeding adopted to pre hydrate the seeds.